The word learning dynamic assessment protocol (WorLDAP): Exploring speech-language pathologists' perceptions of the acceptability of a novel assessment tool. - Jackson, Emily; Botero, Jamie; Hanavan, Caoimhe; Gent, Rosalie; Hatton, Sharni; Leitão, Suze (International Journal of Speech-Language Pathology, 2025)
Purpose: Few resources are available to support speech-language pathologists (SLPs') dynamic assessment of vocabulary with school-aged children. We developed the Word Learning Dynamic Assessment Protocol (currently undergoing pilot testing). Framed by implementation science, in the current study we worked with speech-language pathologists to explore their perspectives on the acceptability of the Word Learning Dynamic Assessment Protocol. Method: Eight speech-language pathologists who work with school-aged children watched a video demonstration of the Word Learning Dynamic Assessment Protocol being administered with a 6-year-old child and were then interviewed to share their thoughts on the Word Learning Dynamic Assessment Protocol's acceptability. Result: Six themes were generated using reflexive thematic analysis: 1) Structure, scripting, and resourcing builds confidence in speech-language pathologists, 2) gaining important insight into the learning process, 3) flexible assessment supports child engagement and diversity, 4) family buy-in is created with clear communication, 5) a worthwhile investment of time?, and 6) building a more tailored assessment. Conclusion: The speech-language pathologists who took part in this study valued the structure and resourcing of the Word Learning Dynamic Assessment Protocol as a way of supporting their ability to evaluate a child's strengths and challenges in vocabulary development in an engaging and individually tailored manner. Suggestions for further development will guide task refinement to meet the needs of speech-language pathologists.